The effects of the varying filling degrees of the stomach on the topographies of the small intestine in cat - Memduh Gezici (Eurasian Journal of Veterinary Sciences)
The purpose of this study was determined the effect of the varying degrees of fullness of the stomach on the topographies of the small intestine in cat; with this aim twenty-four adult cats of different sex and age were used as a material, cats were divided into 3 groups, of which, group 1 had empty, group 2 had halt filled and group 3 had maximum filled stomach, the small intestine were dissected and abdominal cavity was cross sectioned longitudinally and transversally. This investigation is different from that of Deniz and Klesty in that the longitudinal and transversal cross sectiones of the abdominal cavity were done after the materials were deep freezed: the topographies of the small intestine and their relations with the other organs were determined; following dissection the photographes ol the mentioned organs were taken; it was detected that the dudenum and jejunum shifted approximately in Ihree lumbar vertebrae length, ileum in two lumbar vertebrae length caudalty according to the fullness degrees of the stomach in the cat. Furthermore, jejunum was observed to be shifted backward, upward and rightward in the abdominal cavity.